Educación financiera y la toma de decisiones financieras en los microempresarios del campo ferial de artesanías de la ciudad de Iquitos, 2020 - Flores Davila, Andrea Celeste (2022)
The objective of this study was: To determine the relationship between financial education and decision-making in the microentrepreneurs of the handicrafts fair field of the city of Iquitos 2020. Being an applied type research, descriptive - correlational level, and design not experimental. For the investigation, the survey technique and the questionnaire instrument were used to collect information, concluding that financial education is high (32%) because entrepreneurs receive instruction on the management of financial resources; however, forecasting liquidity availability sometimes comes easy to you; In addition, the microentrepreneurs mention that the control of financial performance is always basic for the administration of their finances. At the same time, it has been shown that financial decision-making is rated as regular (30%), since microentrepreneurs mention that the problematic situation is almost never weighted according to the impact on their business; In addition, microentrepreneurs mention that they always verify compliance with the objectives proposed in the decision made. Finally, it was possible to establish a positive relationship between financial education and financial decision making in the microentrepreneurs of the craft fair field of the city of Iquitos, in addition, a correlation coefficient of 0.829 is observed, which is a considerable positive level, where also, a significance of 0.000 is evident.